Propuesta de logística de transporte de rutas alimentadoras para la Universidad de América sede Cerros en Bogotá, Colombia (2021)
The “Fundación Universidad de América” its a higher educational institution, most of the community members must take a walk that lasts around 15 minutes both to arrive to the facilities and to leave them, this creates different problematics for the people that make that walk such as weather problems, additional costs, insecurity and long walk times. Is posed to the Universidad de América a proposal with a solution to the problems mentioned before as the final purpose. The proposal is a feeder route transport logistics for all the university community. Taking into account the aforementioned a survey was made to different university members due to know their perception regarding their mobility needs. With the results obtained a simulation was created to project the feeding routes operation and subsequently the optimal supplier was chosen. Lastly performance indicators were set in order to monitor the service operation. The intention of this proposal is to create value added for the educational service that the University offers raising the university wellness.